Fungsi Keluarga Dalam Upaya Penyembuhan Pasien Gangguan Jiwa yang Dirawat di Rumah Sakit Jiwa Madani Palu - Nurlaelah Umar (Biocelebes, 2008)
Psychoneurotic case in the whole world is expected 0,2 until 0,8% in every year. Support from patient family is very influence in the healing of psychoneurotic patient. This descriptive research was observed the family function in assist the healing proccess of psychoneurotic patient in The Rumah Sakit Jiwa Madani, Palu. Purposive sampling was used to this research and data analized by univariat analized. Sixthy seven patients was participated.The healing of psychoneurotic patient based on the psychologycal function are 54 patients (80,6%) and based on the economycal function are 45 patients (67,2%). The result showed that the family function on the healing of psychoneurotic patient based on the psychologycal function and economycal function is well. Key words: Family function, Healing, Psychoneurotic.